Knowledge, attitudes, and practices of orthopedic patients towards COVID-19 outbreak - Canbeyli, İbrahim Deniz; Çırpar, Meriç; Baysan, Caner; Hayvacı Canbeyli, Fatma; Tepe, Ali (Journal of Surgery and Medicine, 2020)
Aim: Public education and awareness levels play a prominent role in effective, timely prevention and control of a public health crisis. We aimed to determine the level and defective sides of knowledge, perceptions, and awareness of the population who were referred to the outpatient clinic of the Orthopedics and Traumatology on pandemic days. Methods: In this prospective cross-sectional study, a total of 467 patients who were referred to the orthopedics outpatient clinic between May 21, 2020 and June 21, 2020 were surveyed. We used the questionnaire which was previously described by Khan et al. A total of 276 volunteer patients aged over 16 years were included. Patients’ knowledge, perceptions, and awareness level regarding COVID-19 were evaluated in terms of spread of the COVID-19 pandemic, prevention, and control policies. Results: Out of these respondents, 58.3% were males and 41.7% were females. Around 50% of patients were aged less than 45 years, while 50% were above 45 years. The majority of the participants (question-5 [n=271; 98.2%], question-6 [n=231; 83.7%], question-7 [n=221; 80.1%]) had knowledge about the name, origin, signs and symptoms of COVID-19 infection, although their knowledge about the spread of coronavirus was relatively low. 225 participants (81.5%) did not receive any form of training or orientation about infection prevention and control. The mean age those who preferred newspapers and advertisements, friends and family, and other sources (51.09 (17.63) years) was higher than those who preferred social media and the internet (37.85 (16.45) years) (P<0.001). Conclusion: There is a lack of information about spread routes, hence, protection from COVID-19 in the society. We suggest that health care providers develop, and release content-checked health education programs that aim to increase the knowledge level among the people and control COVID-19 spread.